A novel capacity controller for a three-evaporator air conditioning (TEAC) system for improved indoor humidity control. (5th April 2016) - Yan, Huaxia; Deng, Shiming; Chan, Ming-yin
Highlights: A novel capacity controller for TEAC systems for improved indoor humidity control is developed. The novel controller was developed by integrating two previous control algorithms. Experimental controllability tests were carried out. Improved control over indoor humidity levels and higher energy efficiency can be achieved. Abstract: Using a multi-evaporator air conditioning (MEAC) system to correctly control indoor air temperatures only in a multi-room application is already a challenging and difficult task, let alone the control of both indoor air temperature and humidity. This is because in an MEAC system, a number of indoor units are connected to a common condensing unit. Hence, the interferences among operation parameters of different indoor units would make the desired control of an MEAC system hard to realize. Limited capacity control algorithms for MEAC systems have been developed, with most of them focusing only on the control of indoor air temperature, and no previous studies involving control of indoor air humidity using MEAC systems can be identified. In this paper, the development of a novel capacity controller for a three-evaporator air conditioning (TEAC) system for improved indoor air humidity control is reported. The novel controller was developed by integrating two previous control algorithms for a dual-evaporator air conditioning system for temperature control and for a single-evaporator air conditioning system for improved indoor humidity control. Experimental controllability tests were carried out and the controllability test results showed that, with the novel controller, improved control over indoor humidity levels and better energy efficiency for a TEAC system could be obtained as compared to the traditional On–Off controllers extensively used by MEAC systems.